Perancangan Pendidikan Islam di Masa Depan: Integrasi Teknologi, Kecerdasan Buatan, Web3, dan Metaverse - Bahij, Muhammad Alfan; Sukari, Sukari (Asian Journal of Islamic Studies and Da'wah, 2025)
The rapid development of information and communication technology has significantly impacted various aspects of life, including Islamic education. This paper aims to design a future model of Islamic education that integrates advancements in technology, artificial intelligence (AI), Web3, and the metaverse. The research method used is a literature review with a qualitative approach. The findings indicate that technology can enhance accessibility, interactivity, and personalization in Islamic education, while AI supports adaptive learning and educational data analysis. Web3 offers decentralization and data security, and the metaverse enables immersive and collaborative learning environments. The implications of this study highlight the need for a curriculum responsive to technological advancements, teacher training, and adequate technological infrastructure to support the implementation of Islamic education in the digital era.